Feedback regulation of Arid5a and Ppar-γ2 maintains adipose tissue homeostasis - Chalise, Jaya Prakash (Proc Natl Acad Sci U S A, 2019)
Immune cells infiltrate adipose tissues and provide a framework to regulate energy homeostasis. However, the precise underlying mechanisms and signaling by which the immune system regulates energy homeostasis in metabolic tissues remain poorly understood. Here, we show that the AT-rich interactive domain 5A (Arid5a), a cytokine-induced nucleic acid binding protein, is important for the maintenance of adipose tissue homeostasis. Long-term deficiency of Arid5a in mice results in adult-onset severe obesity. In contrast, transgenic mice overexpressing Arid5a are highly resistant to high-fat diet-induced obesity. Inhibition of Arid5a facilitates the in vitro differentiation of 3T3-L1 cells and fibroblasts to adipocytes, whereas its induction substantially inhibits their differentiation. Molecular studies reveal that Arid5a represses the transcription of peroxisome proliferator activated receptor gamma 2 (Ppar-γ2) due to which, in the absence of Arid5a, Ppar-γ2 is persistently expressed in fibroblasts. This phenomenon is accompanied by enhanced fatty acid uptake in Arid5a-deficient cells, which shifts metabolic homeostasis toward prolipid metabolism. Furthermore, we show that Arid5a and Ppar-γ2 are dynamically counterregulated by each other, hence maintaining adipogenic homeostasis. Thus, we show that Arid5a is an important negative regulator of energy metabolism and can be a potential target for metabolic disorders.